Exploring spinal muscular atrophy and its impact on functional status: Indian scenario - Meruna Bose; Shrutika Dilip Parab; Samidha M Patil; Nehal A Pandey; Gargi V Pednekar; Sarabjyot Singh Saini (Wolters Kluwer Medknow Publications, 2019)
The present study aimed to find out the effect of disease-related impairments on functional status in individuals with spinal muscular atrophy and identify perceived barriers to undergo physiotherapy. The cross-sectional observational study was conducted on 90 participants from January to March 2018 using validated patient-reported questionnaire via electronic mail, along with Fatigue Severity Scale and ACTIVLIM. Results revealed that difficulty in sitting was due to scoliosis (36%) and muscle weakness (23%), the latter also contributing toward difficulty in standing and walking (59%). Inverse relationship exists between ACTIVLIM measures and fatigue severity scores (r = −0.338, P < 0.05), body mass index (r = −0.225, P < 0.05), age (r = −0.258, P < 0.05), and duration of illness (r = −0.257, P < 0.05). Economic constraints (27%), difficulty in traveling (17%), and lack of family support and mobility (14%) are perceived barriers to undergo physiotherapy. Functional impairments and identified barriers must be addressed as part of rehabilitation.